2009
DOI: 10.1523/jneurosci.1233-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Rapid Sensory Responses in the Human Frontal Eye Field Region

Abstract: Most of what we know about the human frontal eye field (FEF) is extrapolated from studies in animals. There is ample evidence that this region is crucial for eye movements. However, evidence is accumulating that this region also plays a role in sensory processing and that it belongs to a "fast brain" system. We set out to investigate these issues in humans, using intracerebral recordings in patients with drug-refractory epilepsy. Event-related potential recordings were obtained from 11 epileptic patients from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 128 publications
(47 reference statements)
8
61
0
1
Order By: Relevance
“…In our retinotopic paradigm, which emphasized eventrelated responses, we might expect to see the synaptic inputs in the low-frequency bands, including the alpha band, before the spiking outputs and the HGP Ray et al, 2008Ray et al, , 2011. In fact, several studies using event-related potentials reported very early RLs, which might reflect synaptic inputs rather than spiking activity (Chen et al, 2007;Kirchner et al, 2009). Indeed, our VEP analyses replicated these findings (see Fig.…”
Section: Longest Rls In the Alpha Bandsupporting
confidence: 79%
“…In our retinotopic paradigm, which emphasized eventrelated responses, we might expect to see the synaptic inputs in the low-frequency bands, including the alpha band, before the spiking outputs and the HGP Ray et al, 2008Ray et al, , 2011. In fact, several studies using event-related potentials reported very early RLs, which might reflect synaptic inputs rather than spiking activity (Chen et al, 2007;Kirchner et al, 2009). Indeed, our VEP analyses replicated these findings (see Fig.…”
Section: Longest Rls In the Alpha Bandsupporting
confidence: 79%
“…Consistent with these findings, attending to task-relevant stimulus features strongly activates the PPC and the FEF (Corbetta et al, 2000;Hopfinger et al, 2000;Indovina and Macaluso, 2007). As the FEF responds extremely quickly to sensory stimulation, the propagation of task-related modulation of activity through the attention network may have its origin here (Fecteau and Munoz, 2006;Buschman and Miller, 2007;Kirchner et al, 2009).…”
Section: Introductionsupporting
confidence: 57%
“…Eye movements to the memorized color, when compared to onsets in the same condition, led to the shortest saccade latencies. This effect was small (about 40 ms) but significant, and it suggests that object memory is able to influence saccade programming at a very early stage (Kirchner, Barbeau, Thorpe, Régis, & Liégeois-Chauvel, 2009). …”
Section: Discussionmentioning
confidence: 94%